Excessive treadmill training enhances the insulin signaling pathway and glycogen deposition in mice hearts. Issue 2 (15th October 2018) - Oliveira, Luciana da C.; de Morais, Gustavo P.; da Rocha, Alisson L.; Teixeira, Giovana R.; Pinto, Ana P.; de Vicente, Larissa G.; Pauli, José R.; de Moura, Leandro P.; Mekary, Rania A.; Ropelle, Eduardo R.; Cintra, Dennys E.; da Silva, Adelino S. R.
Abstract: Exhaustive and chronic physical exercise leads to peripheral inflammation, which is one of the molecular mechanisms responsible for the impairment of the insulin signaling pathway in the heart. Recently, 3 different running overtraining models performed downhill (OTR/down), uphill (OTR/up), and without inclination (OTR) increased the serum levels of proinflammatory cytokines. This proinflammatory status induced insulin signaling impairment in the skeletal muscle; however, the response of this signaling pathway in the cardiac muscle of overtrained mice was still unknown. Thus, we investigated the effects of OTR/down, OTR/up, and OTR protocols on the protein levels of phosphorylation of insulin receptor β (pIRβ) (Tyr), phosphorylation of protein kinase B (pAkt) (Ser473), plasma membrane glucose transporter‐1 (GLUT1) and GLUT4, phosphorylation of insulin receptor substrate‐1 (pIRS‐1) (Ser307), phosphorylation of IκB kinase α/β) (pIKKα/β (Ser180/181), phosphorylation of p38 mitogen‐activated protein kinase (p‐p38MAPK) (Thr180/Tyr182), phosphorylation of stress‐activated protein kinases‐Jun amino‐terminal kinases (pSAPK‐JNK) (Thr183/Tyr185), and glycogen content in mice hearts. The rodents were divided into naïve (N, sedentary mice), control (CT, sedentary mice submitted to performance evaluations), trained (TR, performed the training protocol), OTR/down, OTR/up, and OTR groups. After the grip force test, the cardiac muscles (ie, left ventricle) were removed and used for immunoblotting and histology. Although the OTR/up and OTR groups exhibited higher cardiac levels of pIRβ (Tyr), only the OTR group exhibited higher cardiac levels of pAkt (Ser473) and plasma membrane GLUT4. On the contrary, the OTR/down group exhibited higher cardiac levels of pIRS‐1 (Ser307). The OTR model enhanced the cardiac insulin signaling pathway. All overtraining models increased the left ventricle glycogen content, with this probably acting as a compensatory organ in response to skeletal muscle insulin signaling impairment. Abstract : Schematic representation summarizing the current data.